2023
DOI: 10.1002/jmv.28869
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of oral antiviral agents in older patients with COVID‐19 based on real‐world data

Abstract: Several randomized controlled trials and real-world cohort studies have demonstrated the efficacies of nirmatrelvir plus ritonavir (NMV-r) and molnupiravir (MOV) in at-risk patients with COVID-19; however, the effectiveness of antisevere acute respiratory syndrome-coronavirus 2 treatments on older patients (≥65 years) remains unclear. This retrospective cohort study aimed to assess the clinical effectiveness of the oral antiviral agents, MOV and NMV-r, in older patients (≥65 years) infected with severe acute r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Patients aged >18 years who had more than two visits to HCOs from 1 January 2022 to 31 March 2024 and were diagnosed with COVID-19 (confirmed by a positive polymerase chain reaction test [laboratory test code with TNX: LAB:9088] or an International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) code U07.1) [ 25 , 26 , 27 ] were included in the study. To ensure consistency in terms of disease severity, patients who died within 90 days or were hospitalized within 7 days after contracting COVID-19 were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Patients aged >18 years who had more than two visits to HCOs from 1 January 2022 to 31 March 2024 and were diagnosed with COVID-19 (confirmed by a positive polymerase chain reaction test [laboratory test code with TNX: LAB:9088] or an International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) code U07.1) [ 25 , 26 , 27 ] were included in the study. To ensure consistency in terms of disease severity, patients who died within 90 days or were hospitalized within 7 days after contracting COVID-19 were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…[18][19][20] Some observation studies also demonstrated that effectiveness of NMV-r in PASC adults with various chronic disease. [21][22][23] Although NMV-r clinical trials have not included participants under the age of 18, the FDA has authorized NMV-r for emergency use in pediatric patients 12 years of age and older who weight at least 40 kg and have COVID-19 with at least one risk factor, such as diabetes, cerebrovascular diseases, chronic kidney disease, or chronic lower respiratory diseases, among others. 24,25 However, there is no study assessing the safety and effectiveness of NMV-r among pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…2 First, some confounding factors, especially for the comorbidities, were not controlled.Based on their instructive suggestions, we updated our analysis using propensity score matching to balance the demographic features, including cardiac arrhythmias, chronic kidney disease, cerebral infarction, heart failure, hyperlipidemia, sleep apnea, and transplantation between the study and groups.Chen et al 1 have drawn attention to the importance of addressing confounding factors, particularly comorbidities, which were underestimated in our study. 2 Taking their valuable suggestions into consideration, we have conducted an updated analysis using propensity score matching to achieve a balance in demographic features between the study and control groups. We expanded more demographic features including cardiac arrhythmias, chronic kidney disease, cerebral infarction, heart failure, hyperlipidemia, sleep apnea, and transplantation.…”
mentioning
confidence: 99%
“…To the Editor, Chen et al 1 raised several concerns about our recent study. 2 First, some confounding factors, especially for the comorbidities, were not controlled.…”
mentioning
confidence: 99%
See 1 more Smart Citation